Watermelon stomach in a patient with primary Sjögren's syndrome - Krstić Miodrag; Alempijević Tamara; Andrejević Slađana; Zlatanović Maja; Damjanov Nemanja; Ivanović Branislava; Jovanović Ivan; Tarabar Dino; Milosavljević Tomica (Vojnosanitetski Pregled)
Introduction. Watermelon stomach (WS) or gastric antral vascular ectasia (GAVE) is a rare cause of upper gastrointestinal bleeding described in a variety of autoimmune disorders. Association of watermelon stomach with Sjögren's syndrome is extremely rare. Case report. We presented a 67-year old female with primary Sjögren's syndrome (SS) who had developed a persistent severe iron-deficiency anemia. An upper gastric endoscopy revealed the presence of gastric antral vascular ectasia (GAVE) as a cause of occult gastrointestinal bleeding. The treatment with argon-plasma coagulation was postponed as the conservative therapy with iron substitution and proton pump inhibitor led to improvement of anemia and hemoglobin levels normalization. Conclusion. This is the first report of WS in a patient with primary SS without the presence of coexisting autoimmune disorder. Recognition of this rare, but clinically important, cause of gastrointestinal bleeding may decrease comorbidity in patients with autoimmune disorders including primary Sjögren's syndrome.